Technology, identity and the creative artist - Rowley, J.; Bennett, Dawn (Macquarie University, 2013)
Most tertiary students dream about their futures at some time during their studies, and the creation of a portfolio can play an important role in the formation of future identity. In today’s culture, technology is rapidly expanding and changing and our society is becoming progressively more networked, digitilised and globalised. Teaching and learning processes are affected by technological developments. and the portfolio has been modified to utilise this technology (Penny & Kinslow, 2006). The process of developing electronic portfolios promoted a technology-enriched environment for creative arts students to cultivate their learning and knowledge. This paper reports from an OLT (formerly ALTC) funded project at its mid-way point. The project is introducing ePortfolios to students through existing curriculum in the creative and performing arts at four universities in Australia. The project forms part of continuing work to research practices in technology supported teaching and learning.